Functional studies of WSSV-shrimphomologs by DS-RNA interference in the shrimp Marsupenaeus japonicas - Maningas, Mary Beth B.; Kondo, Hidehiro; Hirono, Ikuo (2011)
Global shrimp production tripled over the past decade from 750,000 tonnes in the 1990s to more than three billion tonnes over the past five years, severely affecting ecosystems and livelihoods. White spot syndrome virus (WSSV) is a deadly pathogen for shrimp and a major threat to shrimp farming for the last two decades. Elucidation of the underlying mechanism of shrimp virus interaction will be of enormous help in the prevention and management of shrimp viral disease. Double stranded RNA interference (ds-RNAi) is a powerful tool in elucidating gene function in invertebrates, ds-RNAi allows interference with the expression of a gene in a highly sequence specific manner and thus essential genes can be targeted by design, with little or no risk of undesired off-target effects. Eight (8) WSSV-shrimp homologs ORFs (MjORF13, MjORF17, MjORF20, MjORF23, MjORF24, MjORF31, MjORF34, MjORF37) from Kuruma shrimp previously identified to have significant homology with WSSV were studied using dsRNA interference technology. The eight WSSV-shrimp homologs were successfully amplified, sequenced and dsRNA have been produced. Interestingly, initial results showed that shrimp injected with MjORF31- and MjORF34-dsRNA significantly increased mortality compared to that of the PBS injected group, highlighting their importance in shrimp survival. Challenge test results with white spot virus syndrome (WSSV) as pathogen showed that shrimp injected with MjORF17- and MjORF20-, MjORF23- and MjORF34-dsRNA have higher survival rate than those of the control. Hence, dsRNAs of these four WSSV-shrimp homologs may have protective effect on shrimp against WSSV infection. It would be interesting to pursue or assess the stability and the possible therapeutic application of dsRNAi in shrimp.
Keywords: Shrimps